Laser cladding metal matrix composite wear-resistant powder and composite cladding layer

By using the combination of WC, Cr3C2-20NiCr and VC powder in laser cladding, the problems of second phase particle selection and performance maintenance, the balance of powder particle size and powder feeding fluency, high powder preparation cost and pore defects in the cladding layer are solved, and the preparation of laser cladding metal-based composite wear-resistant powder with high hardness, wear resistance and low cost are achieved.

CN119657913APending Publication Date: 2025-03-21NAT INST CORP OF ADDITIVE MFG XIAN
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411941431.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

In the laser cladding process, it is difficult for the prior art to maintain the performance of the second phase particles, the balance between the powder particle size and the fluency of the feeding, the high cost of powder preparation, and the pore defects of the cladding layer.

Method used

The enhanced phase additive powder consisting of WC powder, Cr3C2-20NiCr powder and VC powder was used to adjust its content and particle size, combined with preparation processes such as plasma rotary electrode method and aerosolization method, laser clad metal-based composite wear-resistant powder with high hardness, wear resistance and low cost were prepared.

Benefits of technology

The effective selection and performance maintenance of the second phase particles during laser cladding is achieved, the overall hardness and wear resistance of the cladding layer are improved, the material cost is reduced, and the porosity is regulated to adapt to different working conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses laser cladding metal matrix composite wear-resistant powder and a composite cladding layer, and belongs to the technical field of laser cladding composite materials. The laser cladding metal matrix composite wear-resistant powder comprises, by weight, strengthening phase adding powder and metal matrix phase powder, the strengthening phase adding powder is composed of, by weight, 3%-50% of WC powder, 5%-45% of Cr3C2-20NiCr powder and 0.2%-5% of VC powder, the total content of the strengthening phase adding powder does not exceed 60%, and the balance metal matrix phase powder. The method is used for solving the problems of selection and performance maintenance of second-phase particles in the laser cladding process, balance between the powder particle size and powder feeding smoothness, high powder preparation cost and cladding layer pore defects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of laser cladding composite materials, and in particular relates to a laser cladding metal-based composite wear-resistant powder and a composite cladding layer. Background Art

[0002] Laser cladding is a material processing method that adds external materials to the molten pool formed by laser irradiation of the substrate and allows the two to solidify together quickly. Due to its advantages of low dilution rate, small heat-affected zone, and relatively small thermal stress and thermal deformation caused by cladding, it has been widely used in additive manufacturing and additive remanufacturing of metal materials.

[0003] In the field of laser cladding to prepare surface wear and corrosion resistance, according to different application requirements, phase transformation strengthening (martensitic phase transformation strengthening), precipitation strengthening, and second phase strengthening principles are often used to prepare cladding layers with different properties. Among them, adding high-hardness second-phase hard metal ceramic particles such as tungsten carbide (WC), chromium carbide (Cr3C2), titanium carbide (TiC), vanadium carbide (VC) and tantalum carbide (TaC) to metal powder to prepare metal-based composite powders to prepare wear-resistant and corrosion-resistant protective layers is currently a common method to improve the wear and corrosion resistance of cladding layers. In metal-based composite cladding layers, metal acts as a bonding phase to connect the matrix and fix the second-phase particles. The metal ceramic particles are firmly fixed in the cladding layer. It is usually hoped that the second-phase metal ceramic particles will maintain their original properties as much as possible, with less decomposition and oxidation, and have good wettability with the metal bonding phase to ensure a firm bond between the two.

[0004] As the commonly used Ni / Co+ WC / Cr3C2 / TiC / VC / TaC metal-based wear-resistant powder, the composition, properties, content, morphology and distribution of the second phase metal ceramic particles have an important influence on the performance of the cladding layer. It is a very important performance control method to regulate the morphology and distribution of the second phase particles by selecting material types, controlling the powder particle composition and adjusting the hard phase.

[0005] At present, most metal-based wear-resistant materials are added with different second-phase metal ceramic materials according to the use requirements (hardness, high temperature resistance), such as cobalt-based tungsten carbide (Co-WC) for room temperature wear-resistant layer, nickel-chromium-based chromium carbide (NiCr- Cr3C2) for high temperature wear-resistant and corrosion-resistant layer, etc., which can meet the requirements of wear resistance under different working conditions. While VC, TaC and TiC are used as hard phases, they can significantly refine the matrix phase grains and improve the impact resistance and wear resistance of the cladding layer.

[0006] The physical properties of different carbides are shown in Table 1. Although WC has a high melting point and hardness, its thermal expansion coefficient (3.8-3.9) is quite different from that of the commonly used matrix materials, such as iron, nickel and alloys (11-14). It is easy to produce large residual stress in the cladding layer, causing cracking. In addition, WC will be obviously oxidized at 500°C. The high temperature caused by local friction during the preparation of laser cladding layers and use will cause obvious oxidation. Its cladding layer can only be used in medium and low temperature environments. Cr3C2 has a low hardness and insufficient wear resistance, and it is difficult to meet the working conditions with high requirements for wear resistance. Although TiC has a high hardness, it has poor wettability with metal solutions such as iron, cobalt and nickel, and its hardness drops sharply after exceeding 500°C. It can only be used for wear-resistant coatings at room temperature. Tantalum is a rare metal and is expensive. The use of TaC and (Ta, Nb) C powder will increase material costs.

[0007] Due to the obvious differences in thermal expansion coefficient, melting point, operating temperature, toughness and corrosion resistance of different second phase materials, it is difficult to take into account both the processability and performance requirements of laser cladding by using the current single second phase particles, which can easily cause problems such as pores, cracks, and insufficient wear resistance in the cladding layer.

[0008] In addition, in order to maintain the smoothness of powder feeding, the particle size of powder used for laser cladding is generally required to be no less than 20μm. Too small a powder particle size can easily lead to particle agglomeration and block the powder feeding tube. The powder morphology is spherical or nearly spherical. Powder particles with irregular shapes can easily block the powder feeding nozzle or uneven powder feeding. This limits the particle size of the second phase powder particles, making it difficult to use fine nano-level powders to strengthen the cladding layer, and loses a means of strengthening the dispersed distribution of fine particles. At present, TaC and TiC powders are mostly nano and micron-level fine powders prepared by chemical methods. Due to their extremely high melting points, their preparation cannot meet the requirements of laser cladding powder feeding. They are mostly added to the matrix phase metal by alloying methods, which is complex and costly. In addition, other methods for preparing large-particle powders, such as atomization and plasma rotating electrode methods, are extremely expensive and are not suitable for large-scale addition as the second phase.

[0009] In summary, how to optimize the selection and performance maintenance of second phase particles during laser cladding, the balance between powder particle size and powder feeding smoothness, powder preparation cost, and porosity defects in the cladding layer are technical problems that need to be solved by existing technologies. Summary of the invention

[0010] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a laser cladding metal-based composite wear-resistant powder and a composite cladding layer to solve the problems of second phase particle selection and performance maintenance in the laser cladding process, the balance between powder particle size and powder feeding smoothness, the high cost of powder preparation and the porosity defects of the cladding layer.

[0011] In order to achieve the above object, the present invention adopts the following technical solutions: The present invention provides a laser cladding metal-based composite wear-resistant powder, which comprises, by weight percentage, a reinforcing phase additive powder and a metal matrix phase powder, wherein the reinforcing phase additive powder consists of 3-50 wt% of WC powder, 5-45 wt% of Cr3C2-20NiCr powder and 0.2-5 wt% of VC powder, and the total content of the reinforcing phase additive powder does not exceed 60wt%, and the remainder is the metal matrix phase powder.

[0012] In one embodiment, the reinforced phase additive powder and the metal matrix phase powder are included in weight percentage, wherein the reinforced phase additive powder is composed of 5-40 wt% WC powder, 5-45 wt% Cr3C2-20NiCr powder and 0.2-5 wt% VC powder, and the total content of the reinforced phase additive powder does not exceed 60 wt%, and the balance is the metal matrix phase powder.

[0013] In one embodiment, the WC powder is a dense spherical particle prepared by a plasma rotating electrode method, and the density of the WC powder particles is not less than 95%.

[0014] In one embodiment, the particle size of the WC powder is 20-150 μm.

[0015] In one embodiment, the Cr3C2-20NiCr powder is spherical loose porous particles obtained by drying the agglomerated granulated particles, and the density of the Cr3C2-20NiCr powder particles is 40-80%.

[0016] In one embodiment, the original diameter of the granulated particles is 100 nm to 2 μm.

[0017] In one embodiment, the VC powder is spherical dense particles prepared by aerosolization, and the density of the VC powder particles is not less than 95%.

[0018] In one embodiment, the particle size of the VC powder is 20-50 μm.

[0019] In one embodiment, the metal matrix phase powder is spherical powder of Ni, Co, Cr or Ni-Cr, or nearly spherical powder of Ni, Co, Cr or Ni-Cr; and the particle size of the metal matrix phase powder is 30-150 μm.

[0020] The present invention also provides a composite cladding layer obtained by laser cladding metal-based composite wear-resistant powder.

[0021] Compared with the prior art, the present invention has the following beneficial effects: The reinforcing phase added powder in the laser cladding metal-based composite wear-resistant powder provided by the present invention is composed of WC powder, Cr3C2-20NiCr powder and VC powder. WC is selected as one of the reinforcing phases, but it is not used alone, but used in combination with Cr3C2-20NiCr powder and VC powder. It can solve the obvious differences in thermal expansion coefficient, melting point, use temperature, toughness, and corrosion resistance of different second-phase materials. The use of a single second-phase particle is difficult to meet the preparation process and use performance requirements of the laser cladding layer. The above combination can make full use of the high hardness of WC and good wettability with the matrix, and at the same time, make up for its thermal expansion coefficient mismatch and easy oxidation by adding other powders. By adjusting the content of WC (3-50 wt%, preferably 5-40 wt%), the residual stress and cracking risk caused by the difference in thermal expansion coefficient can be reduced while ensuring the hardness. In addition, the reinforcing phase added powder is used in combination to improve the overall hardness of the cladding layer through composite strengthening. The present invention does not select TiC as the strengthening phase, but selects WC and Cr3C2-20NiCr with good wettability with the substrate and stable high-temperature performance as the main strengthening phases. Cr3C2 has excellent corrosion resistance and heat resistance and a thermal expansion coefficient similar to that of metal, which can reduce the hardness gradient in the cladding layer, improve the drawbacks of limited addition of a single strengthening phase, limited wear resistance improvement, and cracking caused by a large difference in thermal conductivity with the substrate metal. The addition of VC powder can not only refine the grains, but also have a thermal expansion coefficient similar to that of the substrate metal to improve the high-temperature performance of the cladding layer. In addition, expensive tantalum and its compounds (such as TaC, (Ta, Nb) C, etc.) are not used, thereby reducing material costs. By adjusting the content of the strengthening phase (WC, Cr3C2-20NiCr, VC), the comprehensive properties of the cladding layer, such as hardness, wear resistance, corrosion resistance, heat resistance and cracking resistance, can be regulated to meet the needs under different working conditions. By adjusting the content of the reinforcing phase, the size and number of pores in the cladding layer can also be controlled to prepare coatings with different porosities for special working conditions (such as oil storage coatings).

[0022] Furthermore, in view of the problem of powder feeding smoothness caused by the limitation of powder particle size and morphology during laser cladding, as well as the problem of limited nano-level powder strengthening means and high cost of traditional preparation methods, the composite wear-resistant layer provided by the present invention fully considers the requirements of powder feeding smoothness, and selects powder with a particle size of not less than 20μm to avoid particle agglomeration and clogging of the powder feeding tube. At the same time, through precise particle size control, the powder particle size is ensured to be within the range required by the laser cladding process, which not only ensures the smoothness of powder feeding, but also meets the requirements of the cladding layer performance. Spherical or nearly spherical powders are used to reduce the problem of irregular shaped powder particles clogging the powder feeding nozzle or uneven powder feeding. Through special powder preparation processes (such as plasma rotating electrode method, gas atomization method, etc.), powders with high sphericity and good fluidity are prepared to ensure the stability and reliability of the powder feeding process.

[0023] More specifically, the dense spherical WC powder prepared by the plasma rotating electrode method has a high density and sphericity, which helps to reduce the porosity in the cladding layer and improve the density, thereby further reducing the risk of cracking. The Cr3C2-20NiCr powder is prepared into loose and porous spherical particles by the agglomeration granulation process. This structure can be dispersed into fine Cr3C2 particles during the cladding process and dispersed in the cladding layer, which plays a role in refining the grains and organization, thereby improving the hardness. The selected WC, Cr3C2-20NiCr and VC powders can all be obtained by relatively low-cost preparation methods (such as plasma rotating electrode method, agglomeration granulation, gas atomization method, etc.), further reducing the material cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is the surface morphology of Cr3C2-20NiCr powder; Figure 2 This is the cross-sectional morphology of Cr3C2-20NiCr powder; Figure 3 This is the internal structure diagram of the cladding layer of in625+5wt%WC+45wt%Cr3C2-20NiCr+1wt%VC; Figure 4 This is the internal structure diagram of the cladding layer of in625+15wt%WC; Figure 5 This is the internal structure diagram of the cladding layer of ST6+20wt%WC+30wt%Cr3C2-20NiCr+3wt%VC; Figure 6 This is the internal structure diagram of the cladding layer of ST6+30wt%WC; Figure 7 The internal structure diagram of the cladding layer is 2Cr13+3wt%WC+10wt%Cr3C2-20NiCr+0.5wt%VC; Figure 8 This is the internal structure diagram of the cladding layer of 2Cr13+10wt%Cr3C2-20NiCr+0.5wt%VC. DETAILED DESCRIPTION

[0025] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0026] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0027] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0028] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”

[0029] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0030] The physical properties of different carbides in the prior art are shown in Table 1 below.

[0031] Table 1 Physical properties of common metal carbides

[0032] The present invention is described in further detail below: The present invention provides a laser cladding metal-based composite wear-resistant powder. The laser cladding metal-based composite wear-resistant powder is a powder for multi-material and multi-structure composite reinforced laser cladding. Through the composition of raw powder materials, powder particle structure design and component content control, the preparation of a cladding layer with high wear resistance and corrosion resistance, uniform performance and controllable porosity is achieved, so that the performance of the cladding layer is improved and can adapt to more application environments.

[0033] Specifically, the present invention provides a laser cladding metal-based composite wear-resistant powder, which includes, by weight percentage, a reinforcing phase additive powder and a metal matrix phase powder, wherein the reinforcing phase additive powder is composed of 3-50 wt% of WC powder, 5-45 wt% of Cr3C2-20NiCr powder and 0.2-5 wt% of VC powder, and the total content of the reinforcing phase additive powder does not exceed 60 wt%, and the balance is the metal matrix phase powder.

[0034] The above-mentioned laser cladding metal-based composite wear-resistant powder includes a reinforcing phase added powder and a metal matrix phase powder. It is a metal-based wear-resistant powder material with a reinforcing phase composed of a plurality of second-phase hard phase powder particles of different types and structures. It can be used for the preparation of wear-resistant and corrosion-resistant laser cladding layers. By adjusting the proportion, the structure and performance of the high-hardness and high-wear-resistant cladding layer can be regulated. The inventive point of the present invention mainly lies in the material type of the hard phase powder particles used, the preparation method of different hard phases, the microstructure, and the adjustment of the hard phase content.

[0035] The present invention provides a laser cladding metal-based composite wear-resistant powder and a composite cladding layer prepared by laser cladding using the powder. Dense spherical WC powder, granulated loose Cr3C2-20NiCr powder and VC powder prepared by gas atomization are selected as strengthening additive phases. On the one hand, the high hardness of WC and good wettability of the matrix, the excellent corrosion and heat resistance of Cr3C2 and the thermal expansion coefficient close to that of metal can be fully utilized to reduce the hardness gradient in the cladding layer, improve the disadvantages of limited addition amount of a single strengthening phase, limited improvement of wear resistance and cracking caused by too large difference in thermal conductivity with the matrix metal; on the other hand, the dense WC particles with high melting point and high density are used to improve the hardness of the cladding layer, and can also The molten pool is fully stirred to promote gas overflow and component homogenization. After the granulated loose Cr3C2-20NiCr powder particles are heated, the low-melting-point NiCr alloy is first clad, and the granulated powder is dispersed into fine Cr3C2 particles dispersed in the cladding layer, which plays a role in refining grains and organization; thirdly, VC, as a small amount of added component, has the best grain refining effect in carbide cemented carbide, and at the same time has a thermal expansion coefficient similar to that of the base metal, and has good high temperature resistance; finally, by adjusting the content of the strengthening phase, the size and number of pores in the cladding layer can be regulated to prepare coatings with different porosities for special working conditions, such as oil storage coatings. The combined effect of these factors can improve the shortcomings of the current metal-based composite wear-resistant powder materials. By further regulating the content of the hard phase, a wear-resistant and corrosion-resistant protective layer with better performance and a wider range of applications can be prepared.

[0036] More preferably in the above technical solution, the laser cladding metal-based composite wear-resistant powder includes, by weight percentage, a strengthening additive phase powder and a metal matrix phase powder, wherein the strengthening additive phase powder is composed of 5-40 wt% of WC powder, 5-45 wt% of Cr3C2-20NiCr powder and 0.2-5 wt% of VC powder, and the total content of the strengthening phase additive powder does not exceed 60 wt%, and the balance is metal metal matrix phase powder.

[0037] The content of each component of laser cladding metal-based composite wear-resistant powder is as follows: The content of the reinforcing phase added powder is as follows: WC content does not exceed 5-40 wt %, Cr3C2-20NiCr content does not exceed 45wt%, VC content does not exceed 5%, the total content of the three does not exceed 60wt%, and the rest is metal matrix phase powder.

[0038] The composition of the metal-based composite powder material is as follows: the metal matrix phase powder is Ni, Co, Cr or Ni-Cr spherical or nearly spherical powder with a particle size of 30-150 μm; the strengthening phase added powder is WC, Cr3C2-20NiCr and VC spherical or nearly spherical powder.

[0039] Among them, the structure of the strengthening added phase powder particles is as follows: WC powder is a spherical casting dense particle prepared by plasma rotating electrode method. The density of WC powder particles is not less than 95%, and the particle size is 20-150μm. Cr3C2-20NiCr powder is a spherical loose porous particle after agglomeration and granulation drying. The original diameter of the granulated particles is 100nm-2μm. The density of Cr3C2-20NiCr powder particles is 40%-80%. The surface and cross-sectional morphology of Cr3C2-20NiCr powder are as follows: Figure 1 and Figure 2 As shown, VC powder is spherical dense particles prepared by aerosol method, the density of VC powder is not less than 95%, and the particle size is 20-50μm.

[0040] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0041] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.

[0042] Example 1 The metal matrix phase powder adopts in625 high temperature alloy spherical powder, and the strengthening phase added powder is composed of WC content 5wt%, Cr3C2-20NiCr content 45wt%, and VC content 1wt%.

[0043] The above-mentioned metal matrix phase powder and reinforcement phase added powder are used to prepare the composite cladding layer in the following manner: the total powder feeding amount is 13g / min, 45# matrix, laser power is 1200W, cladding speed is 0.02m / s, overlap rate is 43%, and the internal structure of the prepared composite cladding layer is as follows: Figure 3 As shown in the figure, the cladding layer is about 800μm thick, well bonded to the 45# substrate, with a small number of small holes distributed inside, no cracks, and evenly distributed WC particles, and well bonded to the substrate in625. Its hardness and wear resistance far exceed those of the cladding layer with 15wt% WC content. Under the same conditions, when 15wt% WC powder is added alone, Figure 4 As shown, cracking may occur.

[0044] Example 2 The metal matrix phase powder is a spherical powder of a Stellite 6 (ST6) high temperature alloy, and the strengthening phase added powder is composed of a WC content of 20wt%, a Cr3C2-20NiCr content of 30wt%, and a VC content of 3wt%.

[0045] The above-mentioned metal matrix phase powder and strengthening phase added powder are used to prepare the composite cladding layer in the following manner: the total powder feeding amount is 20g / min, the gray cast iron HT350 matrix, the matrix preheating temperature is 200-250℃, the laser power is 1300W, the cladding speed is 0.01m / s, the overlap rate is 40%, and the internal structure of the cladding layer is as follows: Figure 5 shown.

[0046] The total thickness of the cladding layer is about 1.5 mm, which is well bonded to the substrate and has almost no defects such as pores and cracks. Under the same conditions, when 30% WC is added, Figure 6 As shown, obvious cracks appear, and its wear and impact resistance is significantly lower than the former.

[0047] Example 3 The metal matrix phase powder is 2Cr13 martensitic stainless steel spherical powder, and the strengthening phase added powder is composed of 3wt% WC content, 10wt% Cr3C2-20NiCr content, and 0.5wt% VC content.

[0048] The above-mentioned metal matrix phase powder and reinforcement phase added powder were used to prepare the composite cladding layer in the following manner: the total powder feeding amount was 13 g / min, the cast iron matrix, the laser power was 1200 W, the cladding speed was 0.02 m / s, the overlap rate was 40%, and the internal structure of the cladding layer was as follows: Figure 7 As shown. Figure 8 Compared with the WC without addition shown, the internal porosity is significantly reduced.

[0049] Example 4 The metal matrix phase powder adopts Ni35 nickel-based self-fluxing alloy spherical powder, and the strengthening phase added powder is composed of WC content 50wt%, Cr3C2-20NiCr content 9wt%, and VC content 1wt%.

[0050] The above-mentioned metal matrix phase powder and reinforcement phase added powder were used to prepare the composite cladding layer in the following manner: the total powder feeding amount was 20 g / min, the 2Cr13 substrate was preheated to 300°C, the laser power was 2200 W, the cladding speed was 0.05 m / s, the overlap rate was 53%, and the prepared cladding layer was well bonded to the substrate without cracks.

[0051] Example 5 The metal matrix phase powder is 316 stainless steel alloy spherical powder, and the strengthening phase added powder is composed of WC content 40wt%, Cr3C2-20NiCr content 15wt%, and VC content 2wt%.

[0052] The above-mentioned metal matrix phase powder and reinforcement phase added powder were used to prepare the composite cladding layer in the following manner: the total powder feeding amount was 16 g / min, the 316 stainless steel substrate was preheated to 200°C, the laser power was 1800 W, the cladding speed was 0.05 m / s, the overlap rate was 50%, and the prepared cladding layer was well bonded to the substrate without cracks.

[0053] In summary, it can be seen from Examples 1, 2, 3 and their corresponding comparisons that the present invention uses a variety of second phase reinforcement particles with different properties (density, thermal expansion coefficient, melting point) to compositely strengthen the cladding layer, which can adjust the microstructure and comprehensive properties (wear resistance, corrosion resistance, heat resistance, crack resistance) of the cladding layer in a large range; and the wear-resistant layer prepared by using the above raw material powder can be used at room temperature and high temperature; using high melting point spherical casting dense carbide powder and nano-particle agglomerated nearly spherical chromium carbide powder as the composite second phase, the tungsten carbide particles have a high density, and after being injected into the molten pool, the molten pool can be fully stirred to reduce the porosity; the agglomerated chromium carbide is dispersed to become fine nano-micron particles, which play a role of dispersion strengthening and help to refine the grains; VC can not only inhibit the growth of partially melted chromium carbide grains, but also refine the matrix metal phase structure, and can further regulate the thermal expansion coefficient of the cladding layer; by adjusting the strengthening phase content, the porosity content of the cladding layer can be regulated to meet the needs of special applications.

[0054] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A laser cladding metal-based composite wear-resistant powder, characterized in that: Measured in weight percentage, it includes strengthening phase added powder and metal matrix phase powder, wherein the strengthening phase added powder is composed of 3%-50% WC powder, 5%-45% Cr3C2-20NiCr powder and 0.2%-5% VC powder, and the overall content of the strengthening phase added powder does not exceed 60%, and the balance is metal matrix phase powder.

2. The laser cladding metal-based composite wear-resistant powder according to claim 1, characterized in that: Measured in weight percentage, it includes strengthening phase added powder and metal matrix phase powder, wherein the strengthening phase added powder is composed of 5%-40% WC powder, 5-%45% Cr3C2-20NiCr powder and 0.2%-5% VC powder, and the overall content of the strengthening phase added powder does not exceed 60%, and the balance is metal matrix phase powder.

3. The laser cladding metal-based composite wear-resistant powder according to claim 1 or 2, characterized in that: The WC powder is a dense spherical particle prepared by a plasma rotating electrode method, and the density of the WC powder particles is not less than 95%.

4. The laser cladding metal-based composite wear-resistant powder according to claim 3, characterized in that: The particle size of the WC powder is 20-150 μm.

5. The laser cladding metal-based composite wear-resistant powder according to claim 1 or 2, characterized in that: The Cr3C2-20NiCr powder is spherical loose porous particles after agglomerated granulation particles are dried, and the density of the Cr3C2-20NiCr powder particles is 40-80%.

6. The laser cladding metal-based composite wear-resistant powder according to claim 5, characterized in that: The original diameter of the granulated particles is 100 nm-2 μm.

7. The laser cladding metal-based composite wear-resistant powder according to claim 1 or 2, characterized in that: The VC powder is spherical dense particles prepared by a gas atomization method, and the density of the VC powder particles is not less than 95%.

8. The laser cladding metal-based composite wear-resistant powder according to claim 7, characterized in that: The particle size of the VC powder is 20-50 μm.

9. The laser cladding metal-based composite wear-resistant powder according to claim 1 or 2, characterized in that: The metal matrix phase powder is spherical powder of Ni, Co, Cr or Ni-Cr, or nearly spherical powder of Ni, Co, Cr or Ni-Cr; the particle size of the metal matrix phase powder is 30-150 μm.

10. A composite cladding layer, characterized in that: The metal-based composite wear-resistant powder is prepared by laser cladding according to any one of claims 1 to 9.